On the policy of direct or indirect taxation - Lawson, James A. (Statistical and Social Inquiry Society of Ireland, 1849)
A direct tax can be made to possess all these requisites; it can be made equal, by imposing it on every person according to his means; it can be rendered certain, and can be levied at suitable and convenient times; and it is most productive, the expense of collecting it being small, while all goes directly into the coffers of the state. I would add that direct taxation possesses two other qualities which I think are essential in taxation: first, it does not interfere with the natural course of human industry; and secondly, every man when he is paying a tax knows and feels that he is paying one. Now indirect taxes, by which I mean taxes imposed on commodities instead of on individuals, want two of these four requisites?they are not equal, for they fall only on the consumer of the articles taxed, and are not at all paid by persons in the proportion of their relative means ? and they are not productive, for the collection of them is very expensive, and the payment of them constantly evaded. They differ, however, from direct taxation in the two last respects I have mentioned, and that seems to be their chief recommendation ? they interfere with the natural course of human industry, and they are paid to a great extent unconsciously; they are filched instead of being taken fairly and avowedly. It is in these two latter respects especially, that I wish to contrast the policy of direct and indirect taxation.
The policy of direct or indirect taxation
Read November 20th 1848
Keywords: Personal taxation; Indirect taxation; 314.15